Effects of hallucinogenic drugs on the human heart - Neumann, Joachim; Dhein, Stefan; Kirchhefer, Uwe; Hofmann, Britt; Gergs, Ulrich (Frontiers in Pharmacology, 2024)
Hallucinogenic drugs are used because they have effects on the central nervous system. Their hallucinogenic effects probably occur via stimulation of serotonin receptors, namely 5-HT2A-serotonin receptors in the brain. However, a close study reveals that they also act on the heart, possibly increasing the force of contraction and beating rate and may lead to arrhythmias. Here, we will review the inotropic and chronotropic actions of bufotenin, psilocin, psilocybin, lysergic acid diethylamide (LSD), ergotamine, ergometrine, N,N-dimethyltryptamine, and 5-methoxy-N,N-dimethyltryptamine in the human heart.